PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI YUK WUDU UNTUK MENINGKATKAN ANTUSIASME PEMBELAJARAN PAI BAB WUDU DI SD - Adinda Dwi Agustin; Ardelya Husnianingtyas; Widuri Tresnawati Jatnika; Ani Nur Aeni (FASHLUNA, 2022)
This research is motivated by a condition where there are still many students who have misunderstanding of the ablution material, both from the intention of ablution, the procedure/sequence for ablution, and prayer after ablution. This is related to the learning conditions, namely the lack of enthusiasm from students. The purpose of this study was to increase the enthusiasm of elementary school students in PAI learning, especially the ablution chapter. The Yuk Wudu application learning media was developed as an effort to increase enthusiasm and overcome mistakes when learning ablution material. The research method used is descriptive qualitative with a D&D model and the research procedure is ADDIE. The subjects of this study were students of class II SDN Panyingkiran II, totaling 28 people. The source of the data obtained in this study came from the results of interviews and direct observations of students. As for product validation, it is carried out by PAI teachers. The results of product validity by PAI teachers obtained results of 95% with a very valid / very feasible category. Based on the results of the trials that have been carried out, there was an increase in the enthusiasm of students when learning the wudu chapter PAI material using the Yuk Wudu application.